Chronic pain is associated with a brain aging biomarker in community-dwelling older adults. Issue 5 (May 2019) - Cruz-Almeida, Yenisel; Fillingim, Roger B.; Riley, Joseph L.; Woods, Adam J.; Porges, Eric; Cohen, Ronald; Cole, James
Abstract : Abstract: Chronic pain is associated with brain atrophy with limited evidence on its impact in the older adult's brain. We aimed to determine the associations between chronic pain and a brain aging biomarker in persons aged 60 to 83 years old. Participants of the Neuromodulatory Examination of Pain and Mobility Across the Lifespan (NEPAL) study (N = 47) completed demographic, psychological, and pain assessments followed by a quantitative sensory testing battery and a T1-weighted magnetic resonance imaging. We estimated a brain-predicted age difference (brain-PAD) that has been previously reported to predict overall mortality risk (brain-PAD, calculated as brain-predicted age minus chronological age), using an established machine-learning model. Analyses of covariances and Pearson/Spearman correlations were used to determine associations of brain-PAD with pain, somatosensory function, and psychological function. Individuals with chronic pain (n = 33) had "older" brains for their age compared with those without (n = 14; F[1, 41] = 4.9; P = 0.033). Greater average worst pain intensity was associated with an "older" brain ( r = 0.464; P = 0.011). Among participants with chronic pain, those who reported having pain treatments during the past 3 months had "younger" brains compared with those who did not (F[1, 27] = 12.3; P = 0.002). An "older" brain was significantly associated with decreased vibratory ( r = 0.323; P = 0.033) and thermal ( r = 0.345; P = 0.023) detection, deficient endogenous pain inhibition (F[1, 25] = 4.6; P = 0.044), lower positive affect ( r = −0.474; P = 0.005), a less agreeable ( r = −0.439; P = 0.020), and less emotionally stable personality ( r = −0.387; P = 0.042). Our findings suggest that chronic pain is associated with added "age-like" brain atrophy in relatively healthy, community-dwelling older individuals, and future studies are needed to determine the directionality of our findings. A brain aging biomarker may help identify people with chronic pain at a greater risk of functional decline and poorer health outcomes. Abstract : A clinically relevant, neuroimaging-derived aging biomarker, previously predictive of greater mortality risk during aging, is similarly associated with the complex experience of pain in older individuals.